Imaging modalities and treatment of paediatric upper tract urolithiasis: A systematic review and update on behalf of the EAU urolithiasis guidelines panel. Issue 5 (October 2020) - Grivas, Nikolaos; Thomas, Kay; Drake, Tamsin; Donaldson, James; Neisius, Andreas; Petřík, Aleš; Ruhayel, Yasir; Seitz, Christian; Türk, Christian; Skolarikos, Andreas
Summary: Background: Prompt diagnosis and treatment of paediatric urolithiasis are required to avoid long term sequelae of renal damage. Objective: To systematically review the literature regarding the diagnostic imaging modalities and treatment approaches for paediatric urolithiasis. Study design: PubMed, Science Direct, Scopus and Web of Science were systematically searched from January 1980–January 2019. 76 full-text articles were included. Results: Ultrasound and Kidney-Ureter-Bladder radiography are the baseline diagnostic examinations. Non-contrast Computed Tomography (CT) is the second line choice with high sensitivity (97–100%) and specificity (96–100%). Magnetic Resonance Urography accounts only for 2% of pediatric stone imaging studies. Expectant management for single, asymptomatic lower pole renal stones is an acceptable initial approach, especially in patients with non-struvite, non-cystine stones<7 mm. Limited studies exist on medical expulsive therapy as off-label treatment. Extracorporeal shock wave lithotripsy (SWL) is the first-line treatment with overall stone free rates (SFRs) of 70–90%, retreatment rates 4–50% and complication rates up to 15%. Semi-rigid ureteroscopy is effective with SFRs of 81–98%, re-treatment rates of 6.3–10% and complication rates of 1.9–23%. Flexible ureteroscopy has shown SFRs of 76–100%, retreatment rates of 0–19% and complication rates of 0–28%. SFRs after first and second-look percutaneous nephrolithotomy (PNL) are 70.1–97.3% and 84.6–97.5%, respectively with an overall complication rate of 20%. Open surgery is seldom used, while laparoscopy is effective for stones refractory to SWL and PNL. Limited data exist for robot-assisted management. Conclusions: In the initial assessment of paediatric urolithiasis, US is recommended as first imaging modality, while non-contrast CT is the second option. SWL is recommended as first line treatment for renal stones <20 mm and for ureteral stones<10 mm. Ureteroscopy is a feasible alternative both for ureteral stones not amenable to SWL as well as for renal stones <20 mm (using flexible). PNL is recommended for renal stones >20 mm.